Fecal calprotectin levels used as a noninvasive method for screening for chronic gastritis in pediatric patients. A descriptive study - Demirbaş, Fatma; Çaltepe, Gönül; Abbasguliyev, Hasan; Kalaycı, Ayhan Gazi (São Paulo Medical Journal, 2021)
BACKGROUND: Gastritis consists of inflammation of the gastric mucosa and is one of the main causes of dyspeptic symptoms in children. OBJECTIVE: To investigate the presence of inflammation by evaluating fecal calprotectin (FC) in children diagnosed with chronic gastritis. DESIGN AND SETTING: Descriptive study in Pediatric Gastroenterology Department of Ondokuz Mayis University Hospital in Turkey. METHODS: Between January 2016 and July 2018, FC levels were compared retrospectively in children with chronic gastritis (histopathology-based diagnosis), patients with inflammatory bowel disease (IBD) and healthy children. RESULTS: A total of 67 chronic gastritis patients (61.2% girls) with a mean age of 13.09 ± 3.5 years were evaluated. The mean FC levels were 153.4 μg/g in the chronic gastritis group, 589.7 μg/g in the IBD group and 43.8 μg/g in the healthy group. These levels were higher in chronic gastritis patients than in healthy individuals (P = 0.001) and higher in IBD patients than in the other two groups (P < 0.001). The FC level in the patients with chronic active gastritis (156.3 μg/g) was higher than in those with chronic inactive gastritis (150.95 μg/g) (P = 0.011). Among the patients with chronic active gastritis, the FC level was significantly higher in Helicobacter pylori-positive individuals than in negative individuals (P = 0.031). CONCLUSION: We confirmed the association between increased FC and chronic gastritis. Elevated FC levels may be seen in patients with chronic active gastritis. In order to be able to use FC as a screening tool for chronic gastritis, further studies in a larger study group are needed.